MARCAS FOLKCOMUNICACIONAIS NA OBRA LITERÁRIA DE LUIZ BELTRÃO - Dias, Eliane Penha Mergulhão (2008)
This research is about Folkcomunication in the area of Social Communication, and analyses the literary work Beltrão Luiz, aiming to check how his work produces elements in his studies of Folkcomunication, namely, inside the Theory of the Communication of the Excluded ones (1967). For this study, stories and romances were chosen with the objective of finding in the literary text identification marks of the Folkcomunication, since the proper narrative scheme of Luiz Beltrão, happens frequently, in the presence of the political and ideological discussion between the academic culture and the popular culture, pointing out distinguished social differences. In his literary composition, Luiz Beltrão builds narratives with events that describe the reality of oppressed individuals, disclosing the everyday of these people from the less groups, always in confrontation with forces of political and social. With the theoretical support of Bourdieu (2004), who claims the theory of the fields and develops the concept of habitus, a set of social practical beliefs is established which materializes the identity of the individuals in society, particularly in the group of the excluded ones. Thus, the research has as its objective to check if in the literary composition of Luiz Beltrão there are Folkcomunication elements, as claimed here. The results point that other analyses are necessary to fully confirm the hypotheses; however, it is evident that the choices of the author are always focused on the excluded social groups, without voice in the communicational universe.(AU)